2022
DOI: 10.11606/issn.1678-4456.bjvras.2022.189466
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation dynamics, nutritional quality, and heating capacity of mixed silages of elephant grass (Pennisetum purpureum Schum) and Leucaena (Leucaena leucocephala)

Abstract: Dinâmica fermentativa, qualidade nutricional e capacidade de aquecimento de silagens mistas de capim elefante (Pennisetum purpureum Schum) e leucena (Leucaena leucocephala

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…To determine aerobic stability (AE, h), the methodology adapted by Araújo et al [ 44 ] was used. All procedures were carried out in a closed room, under controlled temperature conditions.…”
Section: Methodsmentioning
confidence: 99%
“…To determine aerobic stability (AE, h), the methodology adapted by Araújo et al [ 44 ] was used. All procedures were carried out in a closed room, under controlled temperature conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Although several studies have demonstrated the positive results of using legumes in silages (Souza et al, 2014;Carvalho et al, 2016;Ribeiro et al, 2020;Araújo et al, 2022), few have considered Pigeon pea. The added of legumes in the silage of annual crops, such as maize, can promote increased levels of CP in silage offered to animals, reinforcing the positive contributions of the presence of legumes to the quality of food (Ligoski et al, 2020) and reducing the cost of acquisition of protein salts and/or concentrates.…”
Section: Introductionmentioning
confidence: 99%